(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Infrastructure projects such as highways, railways, water reservoirs, reclamation etc. requires earth material in very large quantity. In urban areas, borrow earth is not easily available which has to be hauled from a long distance. Quite often, large areas are covered with highly plastic and expansive soil, which is not suitable for such purpose. Extensive laboratory / field trials have been carried out by various researchers and have shownpromising results for application fly ash for this purpose. As fly ash is freely available, for projects in the vicinity of Thermal Power Plants, it can be used as filling material. But it is not suitable as bearing material due to its low shear strength. The present report describes a study carried out to check the improvements in the properties of fly ash with polypropylene fiber in varying percentages. Laboratory trials have been carried out and results are reported in this report. Shear strength of fly ash reinforced with different percentages of polypropylene fiber is checked. Results show the positive effect of addition of fiber in fly ash.